Visual performance with multifocal contact lenses and progressive addition spectacles. Issue 4 (August 2022) - Fogt, Jennifer Swingle; Weisenberger, Kimberly; Fogt, Nick
Abstract: Purpose: As presbyopia occurs, new visual demands create a need for clear vision at multiple distances. Many spectacle wearers adapt into progressive addition lenses (PAL) in order to see clearly at distance, intermediate, and near. A multifocal contact lens provides the ability to see at these same distances without the prismatic effects of a spectacle lens or the peripheral obstruction of a spectacle frame. No studies have been done to date comparing the effect of these types of presbyopic vision correction on a variety of tests of visual performance representative of everyday tasks. Methods: A battery of visual performance tasks were completed by subjects while wearing their habitual PAL spectacles. These subjects were then fit with a multifocal contact lens and wore lenses for 2 weeks or more before completing the tasks again. These functional vision tests included assessments of coincidence anticipation timing, peripheral search and hand-eye coordination, and dynamic visual acuity. Following functional vision testing, subjects completed a preference survey comparing both types of refractive correction while performing common activities of daily living. Results: Performance on the majority of the tests of visual performance were equivalent (P < 0.05) when comparing PAL spectacles and multifocal contact lenses. Survey results demonstrated a preference for multifocal contact lenses overall. Conclusion: PAL spectacles are widely prescribed for presbyopic patients. The findings of this study suggest that in addition to providing excellent vision, multifocal contact lenses provide functional vision performance equal to PAL spectacle wear and patients may prefer them over PAL spectacles.